Advanced development and application of transcritical CO2 refrigeration and heat pump technology—A review. (November 2022) - Song, Yulong; Cui, Ce; Yin, Xiang; Cao, Feng
Abstract: As a highly efficient thermodynamic cycle formed by pure natural fluid and using aerothermal energy, transcritical CO2 technology has huge advantages in terms of energy consumption, equivalent carbon content and environmental benefits, and is an important technological means for global carbon neutrality and renewable energy structure transformation. After reviewing the development history of refrigerants and the basic principle of transcritical CO2 technology, the technical characteristics, research status and development trend of the transcritical CO2 cooling/heating technology in the fields of vehicle air conditioning, building heating, hot water supply, drying industry, commercial cold chain and other fields are comprehensively summarized in details. The main problems in the development of transcritical CO2 technology was summarized regarding different applications with their unique operating conditions and requirements, while corresponding structural modification and thermodynamic parameter optimization schemes have been briefly summarized. As results, it has been proved that CO2 refrigerant has become one of the most important solutions in various applications, and this historical trend has been almost irreversible. Therefore, the future development of the transcritical CO2 technologies, including the system intelligentization and expansion work recovery techniques such as expander, ejector and vortex tube, were carefully analyzed. In summary, the explosive development of the transcritical CO2 technology will be significant for mitigating the contemporary environmental challenges and respecting the regulations on the progressive ban of hydrofluorocarbons (HFCs), so relevant contents are detailed in this paper for providing reference for its further engineering and industrialization. Highlights: The relationship between CO2 refrigerant and the global carbon neutralization was revealed. The current states of transcritical CO2 technique was analyzed from views of various applications. The main problems in the development of transcritical CO2 technology was summarized. Solutions to different constrains were comprehensively summarized in various applications. The future development direction of the transcritical CO2 technology was carefully pointed out.